ANALISIS PENGGUNAAN DAN PENATAUSAHAAN BARANG MILIK DAERAH DI PEMERINTAH KOTA MANADO - Bolendea, Fikha Kristy; Ilat, Ventje; Warongan, Jessy (Universitas Sam Ratulangi, 2017)
Regional Property is one part of the regional Governmentâ€™s assets that are very important to be used and utilized to support the running of the task principal and function of each government agency in the Permendagri 19 year 2016 on guidelines for management of regional property set up government agencies in especially the regional work unit (SKPD) which became the user of regional property to carry out the management of regional property effectively and efficiently. The purpose of this study is to determine the use and administration of local property in the City Government of Manado, especially on the Regional Financial and Asset Management Board. The method used in this research is descriptive analysis method. The results of the research show that the use and appropriation of regional property has been done in accordance with the prevailing regulations and has been running well, even in the inadequate use of assets. To the Head of Manado City BPKAD in order to continue to carry out technical training to the employees so that in the implementation of the use and administration of local property carried out property and in accordance with Permendagri 19 year 2016.Keywords:Â usage and administration of regional property